A pure thermal model to evaluate heat-affected zone when milling E-glass fiber-reinforced polyester composites. (September 2017) - Mkaddem, Ali; Zain-ul-Abdein, Muhammad; Demirci, Ibrahim; Bin Mahfouz, Abdullah S
This paper aims at investigating the resistance-to-vitrification of glass fiber-reinforced plastics when milling. A three-dimensional thermal model using volumetric heat source with Gaussian distributed cylindrical flux was developed as DFLUX subroutine and implemented into Abaqus/Standard code. The wheel feed was simulated by the source motion at 250 mm min −1 with spindle speeds of 11, 460, 15, 280, and 19, 100 rpm. Milling tests using abrasive wheel with 10 mm in diameter were conducted on the composite specimens of dimensions 100 × 25 × 4 mm 3 with fibers oriented both parallel and perpendicular to the milling direction. Four equidistant thermocouples were embedded within the medium plane of the specimen in order to measure the temperature histories. Each series of tests was repeated four times under identical conditions. Predictions confronted to measurements demonstrated the validity of the proposed model. Cutting perpendicular to fibers was found favoring in-depth heat dissipation. However, the fibers acted as thermal barriers so as to limit the heat propagation within the composite plate with fibers oriented parallel to the milling direction. The pure thermal analysis was found sufficient to predict the heat-affected zone in the glass fiber-reinforced plastics specimens, which, in fact, is a function of both wheel spindle speed and fiber orientation.